Measuring the Risk on Housing Investment in the Informal Sector: Theory and Evidence from Pune, India - Kapoor, Mudit; le Blanc, David (World Bank, Washington, D.C., 2013)
The authors provide an economic framework to analyze investment in informal housing in developing countries. They consider a simple model of investment in the housing market where investors can choose between two sectors-the formal sector, where physical investment faces no risk of destruction, and the informal sector, where investment in each period is subjected to an exogenous risk of destruction. Construction costs differ between the two sectors. All households are renters. Renters shop for dwelling attributes and do not care about the sector (formal or informal) itself. The model implies that returns on investment, measured by the rent-to-value ration, will be higher in the informal sector. The authors use a survey conducted by the World Bank in Pune, India in 2002. The sample comprises 2,850 households. This survey had the peculiarity of asking the households, regardless of tenure status, questions about the market rent and value of their dwelling. Thus they can calculate individual rates of return for each unit without facing the typical selection bias problems. Comparing the distributions of returns in the informal and formal sectors, the authors obtain the following results: 1) Rates of return are significantly higher in the informal sector, as predicted by the model. 2) These figures imply a perceived risk on housing investment in the informal sector equivalent to an annual destruction rate ranging between 1 and 2 percent. 3) The two distributions of rates of return present highly idiosyncratic components and are not well explained by variables proxying either the strength of informal property rights or lower perceived risks of eviction.